2017
DOI: 10.1007/s11517-017-1706-y
|View full text |Cite
|
Sign up to set email alerts
|

Apnea and heart rate detection from tracheal body sounds for the diagnosis of sleep-related breathing disorders

Abstract: Sleep apnea is one of the most common sleep disorders. Here, patients suffer from multiple breathing pauses longer than 10 s during the night which are referred to as apneas. The standard method for the diagnosis of sleep apnea is the attended cardiorespiratory polysomnography (PSG). However, this method is expensive and the extensive recording equipment can have a significant impact on sleep quality falsifying the results. To overcome these problems, a comfortable and novel system for sleep monitoring based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…But their study detects also heartbeats and movements which gives a more complete monitoring. A more recent study of the same group [9] advance in result with a sensitivity of 92.8% and a specificity of 99.7%. But this algorithm, based on temporal domain with 3 envelopes, needs to scan the entire recording, so it cannot be applied in real-time, and is not adapted to phrenic stimulation system monitoring.…”
Section: Fig 7: Detection Results With Speech and Background Noisesmentioning
confidence: 85%
“…But their study detects also heartbeats and movements which gives a more complete monitoring. A more recent study of the same group [9] advance in result with a sensitivity of 92.8% and a specificity of 99.7%. But this algorithm, based on temporal domain with 3 envelopes, needs to scan the entire recording, so it cannot be applied in real-time, and is not adapted to phrenic stimulation system monitoring.…”
Section: Fig 7: Detection Results With Speech and Background Noisesmentioning
confidence: 85%
“…It can therefore be assumed that the new sleep monitor can be used for simple sleep monitoring and preliminary screening at home. Additionally, previous research proved that the new sleep monitor is also able to diagnose one of the most common sleep disorders OSA [ 19 ], [ 20 ]. Using sleep staging, it is suggested that the monitor can now also be used to diagnose other sleep disorders, such as insomnia, or for a preliminary screening to decide whether a PSG is necessary or not.…”
Section: Discussionmentioning
confidence: 99%
“…This curve can now easily be used to detect breathing cycles and estimate airflow. A broader discussion of the challenges of relating the amount of airflow to tracheal breathing sounds can be found in [ 20 ], [ 31 ], [ 32 ]. With this information, the respiratory features presented in Table 2 (Tab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an attachment of multiple sensors could potentially be inconvenient during sleep. Various contactless technologies were explored for overnight respiratory rate and/or heart rate monitoring including applications of radar [24], WiFi [25], audio recording [26], [27], pressure sensors [28], depth cameras [29], thermal cameras [30], and infrared cameras [31].…”
Section: Introductionmentioning
confidence: 99%